Welfare implications of rising imported food costs in the Caribbean - David Forgenie; Sharon D. Hutchinson; Andrew Muhammad (Journal of Agriculture and Food Research)
Vulnerability to external shocks such as supply shortages, price increases, disasters and political discord has severe implications for Caribbean food and nutrition security and the scale of economic losses. There is a need to understand how food price shocks impact Caribbean consumers, who are particularly vulnerable due to their heavy reliance on imported food. This study assessed the welfare impacts of rising imported food prices on Caribbean consumers using the linear approximated almost ideal demand system (LA-AIDS) model and compensating variation. The welfare implications of rising prices were assessed using three price shocks in: 2006–2008, 2010–2011, and 2020–2021. Hicksian price elasticities revealed that most imported food categories in the Caribbean region have inelastic demand, except for imported meat and seafood which was found to be elastic. Imported cereals and staples and fats and oils were the least responsive to price changes, while imported meat and seafood was highly responsive. The results of the compensating variation revealed that there were significant welfare losses in 2006–2008 and 2010–2011, when food prices drastically increased, as well as during the first year of the COVID-19 pandemic (2020–2021). Between 2006-2008 and 2010–2011, welfare losses were approximately US$1.54 billion and US$692.52 million, respectively, while food price inflation during the first year of the COVID-19 pandemic resulted in losses estimated at US$1.09 billion. This research highlights the need for regional policies to minimize welfare losses from rising food prices, including social safety nets for vulnerable households and investments in domestic agriculture and supply chain resilience.